(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This paper explores the phonological systems of English and Uzbek, highlighting their similarities and differences. Phonology, the study of the sound system of languages, reveals critical insights into linguistic structures and cognitive processes. By comparing the phonemic inventories, syllable structures, stress patterns, and phonological processes of English and Uzbek, this study aims to provide a comprehensive understanding of how these two languages organize and utilize sounds.